2020
DOI: 10.1101/2020.08.10.20172288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of booster BCG vaccination in preventing Covid-19 infection

Abstract: Introduction : The evidence that BCG (bacille Calmette-Guerin) vaccine may increase the ability of the immune system to fight off pathogens other than tuberculosis has been studied in the past. This nonspecific immunity gained our interest, especially after initial reports of less cases in countries with universal BCG vaccination. In hopes of possible protective immunity, all staff of the Emirates International Hospital (United Arab Emirates) were offered a booster BCG vaccine in early March 2020. All the hos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
3
17
0
1
Order By: Relevance
“…17 In fact, BCG revaccination may decrease susceptibility to SARS-CoV-2, as recently shown. 18 BCG vaccination could induce "trained immunity" by activation and reprogramming of innate immune cells via histone modifications and epigenetic reprogramming at the regulatory sites of genes encoding inflammatory cytokines in cells. 19,20 Hematopoietic stem cells and myeloid progenitors in the bone marrow or microbiota in the gut may be also imprinted by BCG-mediated metabolic and epigenetic processes either directly or indirectly and involved in trained immunity, especially when the BCG vaccine is administered at birth.…”
Section: Discussionmentioning
confidence: 99%
“…17 In fact, BCG revaccination may decrease susceptibility to SARS-CoV-2, as recently shown. 18 BCG vaccination could induce "trained immunity" by activation and reprogramming of innate immune cells via histone modifications and epigenetic reprogramming at the regulatory sites of genes encoding inflammatory cytokines in cells. 19,20 Hematopoietic stem cells and myeloid progenitors in the bone marrow or microbiota in the gut may be also imprinted by BCG-mediated metabolic and epigenetic processes either directly or indirectly and involved in trained immunity, especially when the BCG vaccine is administered at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate is (d), the T cell immunity [33]. The memory T cells exposed by the SARS-CoV-2 may work for long-term immune protection against COVID-19 [33], and these effects may be enhanced by the BCG vaccination [34]. This mechanism can be universal and explains the suppression of mortality in many countries.…”
Section: B Covid-19 Spread In July and Augustmentioning
confidence: 99%
“…Equivalent suggestions have been made by other studies supporting the notion of using the BCG vaccine to prevent severe COVID-19 at least in the most vulnerable groups, such as the elderly and healthcare personnel (160,161). Recently, a study in a hospital from the United Arab Emirates demonstrated that a boost with the BCG vaccine in the healthcare workers could reduce the disease caused by SARS-CoV-2 (162).…”
Section: Trained Immunity and Sars-cov-2 Infectionmentioning
confidence: 99%